Expression patterns of the poplar NF-Y gene family in response to Alternaria alternata and hormone treatment and the role of PdbNF-YA11 in disease resistance - Huang, Ying; Ma, Huijun; Wang, Xiaodong; Cui, Tianxiang; Han, Gang; Zhang, Yu; Wang, Chao (Frontiers in Bioengineering and Biotechnology, 2022)
Plant nuclear factor-Y (NF-Y) transcription factors (TFs) are key regulators of growth and stress resistance. However, the role of NF-Y TFs in poplar in response to biotic stress is still unclear. In this study, we cloned 26 PdbNF-Y encoding genes in the hybrid poplar P. davidiana × P. bollena, including 12 PdbNF-YAs, 6 PdbNF-YBs and 8 PdbNF-YCs. Their physical, chemical parameters, conserved domains and phylogeny were subsequently analyzed. The protein–protein interaction (PPI) network showed that the three PdbNF-Y subunits may interact with NF-Y proteins belonging to two other subfamilies as well as other TFs. Tissue expression analysis revealed that PdbNF-Ys exhibited three distinct expression patterns in three tissues. Cis-elements related to stress- responsiveness were found in the promoters of PdbNF-Ys, and most PdbNF-Ys were shown to be differentially expressed under Alternaria alternata and hormone treatments. Compared with the PdbNF-YB and PdbNF-YC subfamilies, more PdbNF-YAs were significantly induced under the two treatments. Moreover, loss- and gain-of-function analyses showed that PdbNF-YA11 plays a positive role in poplar resistance to A. alternata. Additionally, RT‒qPCR analyses showed that overexpression and silencing PdbNF-YA11 altered the transcript levels of JA-related genes, including LOX, AOS, AOC, COI, JAZ, ORCA and MYC, suggesting that PdbNF-YA11-mediated disease resistance is related to activation of the JA pathway. Our findings will contribute to the functional analysis of NF-Y genes in woody plants, especially their roles in response to biotic stress.